PENGARUH PEMBELAJARAN MUATAN LOKAL TERHADAP KARAKTER PESERTA DIDIK SD NEGERI 234 INPRES TAKALAR KOTA - Ishmah Wafiyah; Bhakti Prima Findiga Hermuttaqien; Hotimah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to determine (1) the description of local content learning at SD Negeri 234 Inpres Takalar Kota, (2) the description of students’ character at SD Negeri 234 Inpres Takalar Kota, and (3) the influence of local content learning on students’ character at SD Negeri 234 Inpres Takalar Kota. The research method used is a quantitative approach with an ex post facto design. The population in this study consisted of all students at SD Negeri 234 Inpres Takalar Kota. The sample included 154 students from grades IV, V, and VI, selected using purposive sampling technique. The data analysis techniques used were descriptive statistical analysis and inferential statistical analysis. The results of descriptive analysis showed that local content learning was well received. In addition, the students of SD Negeri 234 Inpres Takalar Kota tend to have positive character traits. The results of inferential analysis using simple linear regression showed that there is a significant influence of local content learning on students’ character. Based on these results, it can be concluded that: (1) local content learning at SD Negeri 234 Inpres Takalar Kota is well accepted and considered interesting by the students, (2) the students of SD Negeri 234 Inpres Takalar Kota tend to have positive character, and (3) there is a significant influence of local content learning on the students’ character at SD Negeri 234 Inpres Takalar Kota.